Adenosine A2A receptor (A2AR) stimulation enhances mitochondrial metabolism and mitigates reactive oxygen species‐mediated mitochondrial injury. Issue 4 (13th February 2020) - Castro, Cristina M.; Corciulo, Carmen; Solesio, Maria E.; Liang, Fengxia; Pavlov, Evgeny V.; Cronstein, Bruce N.
Abstract: In OA chondrocytes, there is diminished mitochondrial production of ATP and diminished extracellular adenosine resulting in diminished adenosine A2A receptor (A2AR) stimulation and altered chondrocyte homeostasis which contributes to the pathogenesis of OA. We tested the hypothesis that A2AR stimulation maintains or enhances mitochondrial function in chondrocytes. The effect of A2AR signaling on mitochondrial health and function was determined in primary murine chondrocytes, a human chondrocytic cell line (T/C‐28a2), primary human chondrocytes, and a murine model of OA by transmission electron microscopy analysis, mitochondrial stress testing, confocal live imaging for mitochondrial inner membrane polarity, and immunohistochemistry. In primary murine chondrocytes from A2AR −/− null mice, which develop spontaneous OA by 16 weeks, there is mitochondrial swelling, dysfunction, and reduced mitochondrial content with increased reactive oxygen species (ROS) burden and diminished mitophagy, as compared to chondrocytes from WT animals. IL‐1‐stimulated T/C‐28a2 cells treated with an A2AR agonist had reduced ROS burden with increased mitochondrial dynamic stability and function, findings which were recapitulated in primary human chondrocytes. In an obesity‐induced OA mouse model, there was a marked increase in mitochondrial oxidized material which was markedly improved after intraarticular injections of liposomal A2AR agonist. These results are consistent with the hypothesis that A2AR ligation is mitoprotective in OA.